Weed ecology in natural and agricultural systems - Booth, Barbara D. (CABI, 2003)
This text book introduces ecological principles, relating them to weed science and weed management. The ecological principles are illustrated by examples taken from weed and invasive species literature. The book is divided into four main sections: population ecology (6 chapters), interactions between populations (3 chapters), community ecology (4 chapters) and a conclusion about the importance of weed ecology to management. There is a glossary of terms, a subject index and a species index. This book is intended for undergraduates and graduates studying plant ecology, weed science and vegetation management.